How trade dampens the impact of financial frictions in the presence of large firms - Chara Vavoura (Economies, 2022)
In this paper we aim, first, to examine how an economy's financial development affects the welfare gains from trade and, second, to uncover how large firms threaten to suppress these gains, through the exertion of market power and their confirmed preferential access to liquidity. To this purpose, we propose a theoretical model of international trade with financial constraints, which are different between large oligopolists and small monopolistic competitors. We show that trade diminishes the impact of credit misallocation and financial frictions and creates welfare gains by intensifying selection and boosting competition. We find that welfare gains are higher under harsher domestic distortions, meaning that trade particularly benefits developing economies, acting as a substitute for financial development. Nevertheless, in the shadow of large firms, gains from trade are diminished, even more so when such firms are rare and, therefore, more powerful. We conclude that international trade is a prerequisite for financial and economic development but the benefits from globalization are not fully reaped unless large-firm entry and competition are facilitated. We trust that our findings are extremely relevant for developing economies, which are often export-oriented, but, at the same time, suffer from severe credit market inefficiencies and a shortage of large incumbents.
Keywords: F12; F13; F6; G20; L10; 330; financial development; firm heterogeneity; international trade; large firms; monopolistic competition; oligopoly